How do presbylarynx and presbycusis affect the Voice Handicap Index and the emotional status of the elderly? A prospective case–control study. Issue 12 (28th December 2021) - Rodrigues Dias, D; Santos, M; Sousa, F; Azevedo, S; Sousa e Castro, S; Freitas, S; Almeida e Sousa, C; Moreira da Silva, Á
Abstract: Objective: To assess the influence of presbylarynx and presbycusis on Voice Handicap Index and emotional status. Methods: A case–control, prospective, observational, cross-sectional study was conducted of patients aged 65 years or older referred to an otorhinolaryngology department from January to September 2020. Presbycusis was assessed by pure tone and vocal audiometry. Each subject underwent fibre-optic videolaryngoscopy with stroboscopy, and presbylarynx was considered when two or more of the following endoscopic findings were identified: vocal fold bowing, prominence of vocal processes in abduction, and a spindle-shaped glottal gap. Each subject completed two questionnaires: Voice Handicap Index and Geriatric Depression Scale (short-form). Results: The studied population included 174 White European subjects, with a mean age of 73.99 years, of whom 22.8 per cent presented both presbylarynx and presbycusis. Multivariate linear regression revealed that only presence and severity of presbylarynx had an influence on Voice Handicap Index-30 scores. However, both spindle-shaped glottal gap and presbycusis influenced Geriatric Depression Scale scores. Conclusion: Presbylarynx has a strong association with the impact of voice on quality of life. Presbylarynx and presbycusis seem to have a cumulative effect on emotional status.